Potential increasing dominance of heterotrophy in the global ocean - K F Kvale; K J Meissner; D P Keller (Environmental Research Letters, 2015)
Autotrophy is largely resource-limited in the modern ocean. Paleo evidence indicates this was not necessarily the case in warmer climates, and modern observations as well as standard metabolic theory suggest continued ocean warming could shift global ecology towards heterotrophy, thereby reducing autotrophic nutrient limitation. Such a shift would entail strong nutrient recycling in the upper ocean and high rates of net primary production (NPP), yet low carbon export to the deep ocean and sediments. We demonstrate transition towards such a state in the early 22nd century as a response to business-as-usual representative concentration pathway forcing (RCP8.5) in an intermediate complexity Earth system model in three configurations; with and without an explicit calcifier phytoplankton class and calcite ballast model. In all models nutrient regeneration in the near-surface becomes an increasingly important driver of primary production. The near-linear relationship between changes in NPP and global sea surface temperature (SST) found over the 21st century becomes exponential above a 2–4 ${\;}^{° }{\rm{C}}$ global mean SST change. This transition to a more heterotrophic ocean agrees roughly with metabolic theory.